Good sensory recovery of the hand in brachial plexus surgery using the intercostobrachial nerve as the donor - Foroni, Luciano; Siqueira, Mário Gilberto; Martins, Roberto Sérgio; Heise, Carlos Otto; Sterman, Hugo, Neto; Imamura, Adriana Yoriko (Arquivos de Neuro-Psiquiatria, 2017)
Objective: Restoration of the sensitivity to sensory stimuli in complete brachial plexus injury is very important. The objective of our study was to evaluate sensory recovery in brachial plexus surgery using the intercostobrachial nerve (ICBN) as the donor.Methods: Eleven patients underwent sensory reconstruction using the ICBN as a donor to the lateral cord contribution to the median nerve, with a mean follow-up period of 41 months. A protocol evaluation was performed.Results: Four patients perceived the 1-green filament. The 2-blue, 3-purple and 4-red filaments were perceptible in one, two and three patients, respectively. According to Highet's scale, sensation recovered to S3 in two patients, to S2+ in two patients, to S2 in six patients, and S0 in one patient.Conclusion: The procedure using the ICBN as a sensory donor restores good intensity of sensation and shows good results in location of perception in patients with complete brachial plexus avulsion.
Keywords: brachial plexus; intercostal nerves; median nerve; nerve transfer; sensation; perception